ANALISIS KANDUNGAN SERAT KASAR PADA TANAMAN KIAMBANG (Salvinia molesta) DENGAN METODE VAN SOEST DI WADUK BATUTEGI TANGGAMUS LAMPUNG - Aryani Ys, Aulia Luthfiana; Widodo, Yusuf; ., Erwanto (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Kiambang (Salvinia molesta) is the weed in Batutegi Dam which its existence andcomposition have potential to be animal feed stuff. Information of crude fiber content, especiallyNDF and lignin of Kiambang in Batutegi Dam is still unknown. This study aimed to: (1)determine the difference of crude fiber content, namely are NDF and lignin in the whole plant,young leaves, young root, old leaves, and old root, (2) determine the highest and the lowest crudefiber content of Kiambang whole plant, young leaves, young root, old leaves, and old root. Thisstudy was held in April – June 2012, located in Batutegi Dam Tanggamus District and Laboratoryof Animal Research Office Ciawi Bogor West Java. This study used descriftive methods with fivetreatments (namely were whole plant, young leaves, young root, old leaves, and old root) and tworeplications. The study result of analysis van soest showed that the highest NDF content was in thepart of Kiambang whole plant, 77.56%, and the lowest contents were in the old root and trunk, asmuch as 68.40%. The highest lignin contents were in the Kiambang old root and trunk, 25.38%,and the lowest content was in the young leaves, 16.62%.